Towards a Penal Law for Religious? (II/4) Consecrated Life in the Light of Pope Francis’s 2021 Reform of Book VI of the CIC: Part II. Special Considerations (4): the Evangelical Counsel of Obedience as the Object of Penal Protection - Skonieczny, Piotr (Prawo Kanoniczne, 2025)
In the final article of the series, the author analyses the protection of the evangelical counsel of obedience, especially in the light of the reformed Book VI CIC/21. Despite different conceptions of obedience within various traditions of consecrated life, its essence remains consistent: the fulfilment of precepts (I.1). Therefore, the norms of universal law are sufficient in this regard, particularly the offence of disobedience under canon 1371, §1 CIC/21 (I.3). Consequently, the penal protection of the counsel of obedience in consecrated life is indirectly provided for as well. Subjects undoubtedly have a duty to denounce certain delicts (II.2) and religious superiors have a duty to discipline their brothers and sisters (II.3). The protection of the vow of obedience is also influenced by the changes made to the delict of abuse of power, ecclesiastical office, and function in consecrated life (canon 1378 §1 CIC/21) (III.2.), the abuse of authority as an element of the delict in canon 1395 §3 CIC/21 in conjunction with canon 1398 §2 CIC/21 (III.3), and the aggravating circumstance in canon 1326 §1, no. 2 CIC/21 (III.1). In conclusion, the author states that the reform of Book VI CIC/21 has not changed the model of protection of consecrated life already present in the 1983 Code. This model provides two levels of protection: first disciplinary, then penal. This model is more practical and, in principle, does not consider theological aspects. Consequently, Pope Francis’ reforms give rise to a disciplinary and canonical conception of consecrated life rather than a theological one. Finally, the recent reform of penal law may be an impetus to start working on the proper law, penal and disciplinary, of individual Institutes of Consecrated Life and Societies of Apostolic Life.